2000
DOI: 10.1128/jcm.38.2.724-726.2000
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Enterococci and Staphylococci on Hospital Fabrics and Plastic

Abstract: The transfer of gram-positive bacteria, particularly multiresistantStaphylococcus aureus (MRSA) and vancomycin-resistant enterococci (VRE), among patients is a growing concern. One critical aspect of bacterial transfer is the ability of the microorganism to survive on various common hospital surfaces. The purpose of this study was to determine the survival of 22 gram-positive bacteria (vancomycin-sensitive and -resistant enterococci and methicillin-sensitive and -resistant staphylococci) on five common hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
358
2
9

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 657 publications
(398 citation statements)
references
References 18 publications
14
358
2
9
Order By: Relevance
“…S. aureus has been shown to survive under nutrient limited conditions for several weeks on various hospital fabrics and plastics, with the longest survival times on polyester and polyethylene plastic [32]. Relatively good survival of S. aureus on polyurethane foam would favour development of reservoirs of infection for this organism in cot mattress material.…”
Section: Discussionmentioning
confidence: 99%
“…S. aureus has been shown to survive under nutrient limited conditions for several weeks on various hospital fabrics and plastics, with the longest survival times on polyester and polyethylene plastic [32]. Relatively good survival of S. aureus on polyurethane foam would favour development of reservoirs of infection for this organism in cot mattress material.…”
Section: Discussionmentioning
confidence: 99%
“…Neely and Maley studied the survival of 22 Gram-positive bacteria, including VRE, MSSA and MRSA, on common hospital materials. 24 They inoculated five types of hospital materials with 10 4 to 10 5 cfu of the different bacteria. The materials included smooth 100% cotton clothing, 100% cotton terry towels, 60% cotton/40% polyester blend scrub suits, 100% polyester privacy curtains and 100% polypropylene plastic aprons.…”
Section: Ppe and Proper Hygienementioning
confidence: 99%
“…In comparison with viruses, bacteria and fungi survive longer (1-90 days) on environmental surfaces. [23][24][25] Several other studies on survival of bacterial (gram negative and positive) and fungal agents on environmental surfaces indicate that the survival of microorganisms is highly variable, ranging from minutes to days. [26][27][28] The results of this study indicate that FCV can survive for 8 to 72 hours, which is longer than the reported survival of poliovirus and HAV.…”
Section: Discussionmentioning
confidence: 99%